Injectable hybrid laponite/alginate hydrogels for sustained release of methylene blue - Li, Yulin (2019)
The incorporation of biocompatible Laponite (LP) into alginate hydrogels greatly increases the drug encapsulation efficiency of methylene blue (MB). By raising the LP content from 0 to 0.5 wt.%, the half-release time (t1/2) of MB in oven-dried gels increases from ~2 h to ~10 h, while t1/2 in vacuum-dried gels slightly changes from ~1 h to ~2 h. Increasing LP content together with drying modes can induce the MB release mechanism froma diffusion-controlled release into a swelling-controlled one.